Reflections of participating in a Students as Partners co-creator project in a second year Physiology subject : An example of an Internationalisation at Home experience. - West, Jan; Gatt, Judzea; Ho, Darren; Nunn, Kyler; Popplewell, Maya (Journal of University Teaching & Learning Practice v.21 n.4 https://doi.org/10.53761/g6txtb83, 2024)
This paper showcases a partnership between students, and an academic to develop new and review existing learning resources in a second-year physiology subject "Systems Physiology" offered at Deakin University in Australia, from the perspective of both of students and the teaching staff. All involved participated in a collaborative, student lead project; it was a reciprocal process where all members contributed, in their own unique way to evaluate, design, create and implement an online activity to enhance the understanding of a concept, in this case cardiovascular physiology (both theoretical and practical aspects). This type of partnership encourages critical reflection and opens a door to new ways of learning and teaching in Higher Education. We propose that Students As Partners project could be designed to specially meet an Internationalisation at Home experience for both domestic and international students at Deakin University tapping into the diverse pool of experiences and skills that our current students already bring to the curriculum. [Author abstract]